Understanding Inflation Inertia in Angola - Kyei, Alexander (IMF Working Papers; Working Paper, 2009)
In recent years, the decline in inflation in Angola has stalled and further steps may be needed to attain the authorities' medium term goal of meeting the Southern African Development Community (SADC) convergence criteria of a low single digit inflation rate. A Vector Error Correction (VEC) model, which analyzes the factors that affect the inflationary process in Angola, suggests that the inflation path has been largely affected by exchange rate movements. This implies that greater exchange rate flexibility that facilitates a gradual appreciation would be instrumental to moderate price growth through reducing the price of imports and limiting liquidity injection by the National Bank of Angola (BNA). Additionally, the analysis shows that excess liquidity, which is measured by positive deviations of M2 from its equilibrium level, adds to demand pressures, and contributes to inflation with a lag. This underlines the importance of closely monitoring the growth of monetary aggregates as well as improving liquidity management.